A wide band gap perovskite solar cell and a preparation method thereof

CN122995394APending Publication Date: 2026-10-27CHINA ELECTRONIC TECH GRP CORP NO 18 RES INST
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610954928.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-30
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0004]本发明的目的是解决宽带隙钙钛矿结晶动力学复杂、成膜均匀性差以及光照或热应力下易发生卤素相分离导致稳定性下降等技术问题,提出一种基于混合氯盐添加剂的宽带隙钙钛矿太阳电池及其制备方法,在实现高质量钙钛矿薄膜制备的同时,兼顾抑制卤素偏析与非辐射复合,提升器件开路电压与长期运行稳定性

Benefits of technology

1、本发明通过在钙钛矿吸收层中添加特定比例的混合氯盐添加剂,显著优化了结晶动力学,减少了中间相的产生,形成了均匀致密且高结晶度的宽带隙钙钛矿薄膜,从而有效降低了非辐射复合损失,为器件获得高开路电压与填充因子奠定了材料基础。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122995394A_ABST
    Figure CN122995394A_ABST
Patent Text Reader

Abstract

The application discloses a kind of wide band gap perovskite solar cell and preparation method thereof, including from bottom to top sequentially stacked substrate, hole transport layer, perovskite absorption layer, electron transport layer and metal electrode, perovskite absorption layer contains mixed chlorides additive, the additive is composed of MACl, PbCl2 and RbCl, the additive amount of three is respectively 5mol%, 2mol% and 2mol% of the total amount of perovskite absorption layer precursor solute.Its preparation method includes the steps of preparing transparent conductive substrate, hole transport layer, perovskite absorption layer, electron transport layer and metal electrode, wherein perovskite absorption layer is prepared by spin coating combined with vacuum flash process.By adding specific proportion of MACl, PbCl2 and RbCl mixed chlorides additive to perovskite absorption layer, the crystallization quality of perovskite thin film can be significantly optimized, halogen phase separation is inhibited, non-radiative recombination is reduced, open-circuit voltage and long-term stability of the cell are improved, and it is suitable for single junction wide band gap perovskite cell and perovskite / crystalline silicon stacked cell top cell preparation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of solar cell technology, specifically relating to a wide-bandgap perovskite solar cell and its preparation method. Background Technology

[0002] Perovskite / crystalline silicon tandem solar cells are becoming one of the most promising photovoltaic technologies due to their significantly improved power conversion efficiency. The key to achieving high-efficiency tandem cells lies in the fabrication of high-quality perovskite top cells. Among numerous candidate light-absorbing materials, perovskites containing mixed cations and mixed halides are currently considered the most promising choice for top cells. However, their complex composition leads to a cumbersome crystallization kinetic process, making it particularly difficult to obtain high-quality wide-bandgap top cells. Taking mixed halide perovskites as an example, multiple intermediate phases during film formation trigger multiple nucleation pathways, making it difficult to form uniform and highly crystalline films. Furthermore, such wide-bandgap perovskites are prone to spontaneous separation of I-rich and Br-rich phases under light or thermal stress, resulting in significant open-circuit voltage loss and impairing the efficiency and stability of tandem devices. Generally, I... - With Br - Differences in ionic radius and electronegativity introduce inhomogeneous stresses into the crystal lattice. Under illumination, photogenerated carriers promote halide ion migration, which tends to segregate towards grain boundaries or defect sites, forming a narrow-bandgap I-rich phase and a wide-bandgap Br-rich phase. This phase separation creates localized carrier traps, exacerbates nonradiative recombination, and thus severely reduces the open-circuit voltage.

[0003] Currently, passivating defects and achieving uniform surface potential through additives and interface engineering to reduce open-circuit voltage loss has become a common strategy. However, the effectiveness of these surface modification methods is limited and fails to reach the bulk phase of the perovskite light-absorbing layer. More importantly, the inherent non-uniform distribution of halide ions within the bulk phase, and the resulting photoinduced phase separation problem, remain fundamental challenges restricting device performance. Summary of the Invention

[0004] The purpose of this invention is to solve the technical problems of complex crystallization kinetics, poor film uniformity, and halogen phase separation under light or thermal stress leading to decreased stability in wide-bandgap perovskites. This invention proposes a wide-bandgap perovskite solar cell based on mixed chloride salt additives and its preparation method. While achieving high-quality perovskite film preparation, this invention also aims to suppress halogen segregation and non-radiative recombination, thereby improving the open-circuit voltage and long-term operational stability of the device.

[0005] To solve the above-mentioned technical problems, the technical solution of the present invention is: a wide-bandgap perovskite solar cell, comprising a substrate, a hole transport layer, a perovskite absorber layer, an electron transport layer, and a metal electrode stacked sequentially from bottom to top. The perovskite absorber layer contains a mixed chloride salt additive, which is composed of MACl, PbCl2, and RbCl. The amount of MACl added is 5 mol% of the total amount of solute in the perovskite absorber layer precursor, the amount of PbCl2 added is 2 mol% of the total amount of solute in the perovskite absorber layer precursor, and the amount of RbCl added is 2 mol% of the total amount of solute in the perovskite absorber layer precursor.

[0006] Furthermore, the band gap of the perovskite absorber layer is 1.65 eV to 1.72 eV.

[0007] Furthermore, a transparent conductive electrode is disposed on the substrate, and the transparent conductive electrode is made of ITO.

[0008] Furthermore, the material of the hole transport layer is any one of 4PADCB, MeO-2PACz, or Me-4PACz.

[0009] Furthermore, the electron transport layer is a composite structure of C60 / BCP / Ag.

[0010] Furthermore, the material of the metal electrode is one of silver, copper, or gold.

[0011] A method for fabricating the above-mentioned wide-bandgap perovskite solar cell includes the following steps: (1) A transparent conductive electrode is fabricated on a substrate using radio frequency magnetron sputtering technology to obtain a transparent conductive substrate; (2) Prepare hole precursor solution. The hole precursor solution is spin-coated on a transparent conductive substrate using spin-coating technology and then annealed to prepare a hole transport layer. (3) A perovskite absorber layer is prepared by spin-coating a perovskite precursor solution onto the hole transport layer using spin-coating and vacuum flash evaporation techniques. The perovskite precursor solution contains a mixed chloride salt additive composed of MACl, PbCl2 and RbCl, wherein the amount of MACl added is 5 mol% of the total solute in the perovskite precursor, the amount of PbCl2 added is 2 mol% of the total solute in the perovskite precursor, and the amount of RbCl added is 2 mol% of the total solute in the perovskite precursor. (4) An electron transport layer is prepared on the perovskite absorber layer using thermal evaporation technology; (5) A metal electrode is prepared on the electron transport layer using thermal evaporation technology.

[0012] Further, in step (3), the specific process for preparing the perovskite absorber layer is as follows: the perovskite precursor solution with mixed chloride salt additives is spin-coated onto the hole transport layer. The spin coating is carried out in two stages. The first stage has a rotation speed of 500 rpm and a duration of 5 to 10 s, and the second stage has a rotation speed of 4000 rpm and a duration of 15 to 25 s. After spin coating, vacuum flash evaporation is performed, the gas pressure is evacuated to 4 Pa ​​and maintained for 30 to 120 s, and then annealing is performed.

[0013] Furthermore, in step (1), the material of the transparent conductive electrode is ITO; in step (2), the material of the hole transport layer is one of 4PADCB, MeO-2PACz or Me-4PACz.

[0014] In further step (4), the electron transport layer is a composite structure of C60 / BCP / Ag; in step (5), the material of the metal electrode is one of silver, copper or gold.

[0015] Compared with the prior art, the beneficial effects of the present invention are as follows: 1. This invention significantly optimizes crystallization kinetics and reduces the generation of intermediate phases by adding a specific proportion of mixed chloride salt additives to the perovskite absorber layer, forming a uniform, dense, and highly crystalline wide-bandgap perovskite film. This effectively reduces non-radiative recombination loss and lays the material foundation for devices to obtain high open-circuit voltage and fill factor.

[0016] 2. The mixed chloride salt additive of the present invention utilizes chloride ions to partially replace iodine ions or bromide ions in the crystal lattice, thereby alleviating the lattice stress caused by the difference in ion size, while passivating defects at grain boundaries and interfaces, suppressing photo-induced halogen segregation, and significantly improving the operational stability of wide-bandgap perovskite top solar cells under continuous illumination or thermal stress.

[0017] 3. The mixed chloride salt additive strategy adopted in this invention not only solves the inherent phase separation problem of wide-bandgap perovskites, but also has the advantages of strong process compatibility and low cost. It can be easily integrated into the existing perovskite / crystalline silicon tandem solar cell fabrication process, providing a practical and feasible technical path for realizing efficient, stable and scalable tandem photovoltaic devices. Attached Figure Description

[0018] Figure 1 This is a schematic diagram of the structure of a wide-bandgap perovskite solar cell with mixed chloride salt additives provided in an embodiment of the present invention.

[0019] Figure 2 This is a graph showing the current-voltage characteristics of a wide-bandgap perovskite solar cell in the embodiments and comparative examples of the present invention. Detailed Implementation

[0020] To gain a deeper understanding of the present invention, preferred embodiments will be described in detail below with reference to specific examples. However, it should be noted that these descriptions are merely for illustrating the features and advantages of the invention and do not impose any limitations on the claims. There are no particular restrictions on the source of all raw materials used in the present invention; they can be purchased from the market or prepared according to conventional methods known to those skilled in the art.

[0021] like Figure 1 As shown, the perovskite solar cell and its preparation method of the present invention are composed of a transparent conductive substrate, a hole transport layer, a perovskite absorber layer, an electron transport layer, and a metal electrode; their positions from top to bottom are metal electrode, electron transport layer, perovskite absorber layer, hole transport layer, and transparent conductive substrate.

[0022] In this embodiment, the metal electrode is deposited with metallic silver (Ag) using vacuum evaporation technology, and its thickness ranges from 100 to 200 nanometers.

[0023] The hole transport layer uses a self-assembled molecular layer, which is at least one of, but not limited to, 4-(7H-dibenzo[c,g]carbazole-7-yl)butylphosphonic acid (4PADCB), [4(3,6-dimethyl-9H-carbazole-9-yl)butyl]phosphonic acid (Me-4PACz) and [2-(3,6-dimethoxy-9H-carbazole-9-yl)ethyl]phosphonic acid (MeO-2PACz).

[0024] When spin-coating perovskite, the solvent used is a mixed solvent composed of N,N-dimethylformamide (DMF) and dimethyl sulfoxide (DMSO) in a ratio of 4:1, and the molar concentration of the perovskite precursor solution for spin-coating is 1.5 mol / L.

[0025] The perovskite precursor solution was mixed with chloride salt additives, the composition and proportion of which were: 5 mol% MACl, 2 mol% PbCl2 and 2 mol% RbCl, while 5 mol% MAPbCl3 additive was used as a control sample.

[0026] The spin coating process is divided into two stages. The first stage has a rotation speed of 500 rpm and a duration of 5-10 seconds. The second stage has a rotation speed of 4000 rpm and a duration of 15-25 seconds. After spin coating, the spin coating is transferred to a vacuum flash evaporator and the pressure is reduced to about 4 Pa ​​and maintained for 30-120 seconds.

[0027] The electron transport layer is composed of fullerene (C60), copper bath (BCP), and thin Ag, which are deposited onto the perovskite layer using vacuum evaporation technology.

[0028] The following is a description with reference to specific embodiments: Example 1 This embodiment provides a method for preparing a wide-bandgap perovskite solar cell with mixed chloride salt additives. The structure of the resulting perovskite solar cell is as follows: Figure 1 As shown, from top to bottom, the layers are a metal electrode, an electron transport layer, a perovskite absorber layer, a hole transport layer, and a transparent conductive substrate.

[0029] The preparation method specifically includes the following steps: Step 1: Pre-treatment of the glass substrate The glass substrate was ultrasonically cleaned with deionized water and ethanol for 30 minutes each. The residual ethanol on the substrate surface was dried with a nitrogen gun and then treated with ultraviolet ozone for 25 minutes.

[0030] Step 2: Prepare a transparent conductive electrode. In this embodiment, indium tin oxide (ITO) was selected as the transparent conductive electrode, and magnetron sputtering was used with a power of 25 and an argon flow rate of 30 for 30 minutes.

[0031] Step 3: Prepare the hole transport layer In this embodiment, 4PADCB is selected as the hole transport layer, and the preparation steps are as follows: Step 3.1: Weigh a certain amount of 4PADCB and dissolve it in anhydrous ethanol to prepare a 4PADCB solution with a concentration of 0.5 mg / mL; Step 3.2: Spin coat the prepared 4PADCB solution onto the substrate surface using a spin coater at a speed of 3000 rpm for 30 seconds. Then anneal it at 100°C for 10 minutes on a high-temperature hot plate to obtain the hole transport layer.

[0032] Step 4: Prepare the perovskite layer This embodiment uses a FA with a bandgap of 1.72 eV. 0.78 Cs 0.22 Pb(I 0.8 Br 0.2 )3, as the perovskite layer, is prepared using the following steps: Step 4.1: Prepare perovskite precursor solution Weigh out 86 mg of CsI, 201 mg of FAI, 165 mg of PbBr2, 505 mg of PbI2, 5.06 mg of MACl, 8.3 mg of PbCl2 and 3.6 mg of RbCl, dissolve them in 1 mL of a mixed solvent, stir overnight at 40 °C to obtain a perovskite precursor solution. The mixed solvent consists of DMF and DMSO, and the volume ratio of DMF to DMSO is 4:1. Step 4.2: Preparation of perovskite thin films The perovskite precursor solution was spin-coated onto the hole transport layer. The spin-coating was performed in two stages: the first stage was set at a spin speed of 500 rpm for 10 s, and the second stage was set at a spin speed of 4000 rpm for 15 s. After spin-coating, the sample was quickly transferred into a vacuum flash evaporator, and the pressure was reduced to about 4 Pa ​​and held for 120 s. After flash evaporation, the substrate material containing the perovskite film was placed on a high-temperature hot stage and annealed at 100 °C for 15 min to obtain the perovskite layer.

[0033] Step 5: Fabrication of the electron transport layer In this embodiment, a C60 / BCP / Ag composite structure is selected as the electron transport layer, which is obtained by sequentially depositing it on the surface of the perovskite layer by vacuum thermal evaporation.

[0034] Step 6: Prepare metal electrodes In this embodiment, metallic silver (Ag) is selected as the metal electrode material. Specifically, a vacuum thermal evaporation process is used to deposit an Ag electrode layer on the electron transport layer. The thickness of the electrode layer is 100 nm.

[0035] The current-voltage characteristic curve of the perovskite solar cell device prepared in this embodiment is as follows: Figure 2 The specific performance parameters are shown in the table below: Table 1. Photovoltaic performance parameters of perovskite solar cell devices using mixed chloride salt additives

[0036] Comparative Example 1 To illustrate the technical effect of the mixed chloride salt additive in this invention, the following comparative example was set up. This comparative example uses the conventional additive MAPbCl3 as a control, with an addition amount of 5 mol% of the total solute in the perovskite precursor. Except for the preparation of the perovskite precursor solution, the battery structure and preparation method are the same as in Example 1.

[0037] The preparation process of the perovskite precursor solution in this comparative example is as follows: 86 mg CsI, 201 mg FAI, 165 mg PbBr2, 505 mg PbI2, 5.06 mg MACl and 20.75 mg PbCl2 were dissolved in 1 mL of mixed solvent (DMF to DMSO volume ratio of 4:1) and stirred overnight at 40 °C to obtain the precursor solution.

[0038] The current-voltage characteristic curve of the perovskite solar cell device prepared in Comparative Example 1 is shown in Figure 1. Figure 2 The specific performance parameters are shown in the table below: Table 2 Photovoltaic performance parameters of perovskite solar cell devices using MAPbCl3 additive

[0039] As can be seen from the specific performance parameters in Tables 1 and 2, introducing mixed chloride salt additives to replace conventional MAPbCl3 can effectively improve the overall photovoltaic performance of perovskite devices. This is because Cl... - The ionic radius is small, which can partially replace I in the crystal lattice. - or Br - The introduction of chloride ions helps to regulate crystallization kinetics, reduce the formation of intermediate phases, and promote a more dense and uniform film. Furthermore, the mixed chloride additives can passivate defects at grain boundaries and interfaces, reduce the activity of ion migration channels, and thus suppress photo-induced halogen segregation. Therefore, this method can effectively reduce non-radiative recombination losses and improve open-circuit voltage and fill factor. The mixed chloride salt additive method proposed in this invention demonstrates significant advantages in terms of film quality and operational stability of wide-bandgap perovskite solar cells. Addressing the technical challenges of inhomogeneous film layers and severe open-circuit voltage decay caused by photo-induced halogen phase separation in traditional mixed halide perovskites due to complex crystallization kinetics, this invention proposes a mixed chloride salt additive scheme composed of MACl, PbCl2, and RbCl in specific proportions (5%, 2%, 2%). This design effectively alleviates the problems caused by I- ion lattice occupancy and defect passivation through the dual effects of chloride ion lattice occupancy and defect passivation. - With Br - The non-uniform lattice stress caused by differences in ionic radii suppresses the segregation tendency of I-rich and Br-rich phases, thereby significantly reducing non-radiative recombination losses. In particular, the mixed chloride additives can also regulate the transformation pathway of the crystalline mesophase, promoting the formation of a dense, uniform, and highly crystalline morphology in the perovskite film, further enhancing the long-term operational stability of the device under continuous illumination or thermal stress. This combination of process compatibility, cost-effectiveness, and significant improvement in electrical performance enables this technology not only to meet the high-efficiency fabrication requirements of single-junction wide-bandgap perovskite solar cells, but also to provide a key material solution for the reliable realization of top cells in perovskite / crystalline silicon tandem solar cells, demonstrating broad application prospects and significant industrialization value in next-generation high-efficiency photovoltaic technologies.

[0040] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A wide-bandgap perovskite solar cell, comprising a substrate, a hole transport layer, a perovskite absorber layer, an electron transport layer, and a metal electrode stacked sequentially from bottom to top, characterized in that, The perovskite absorber layer contains a mixed chloride salt additive, which consists of MACl, PbCl2 and RbCl. The amount of MACl added is 5 mol% of the total solute in the perovskite absorber layer precursor, the amount of PbCl2 added is 2 mol% of the total solute in the perovskite absorber layer precursor, and the amount of RbCl added is 2 mol% of the total solute in the perovskite absorber layer precursor.

2. The wide-bandgap perovskite solar cell according to claim 1, characterized in that, The band gap of the perovskite absorber layer is 1.65 eV to 1.72 eV.

3. The wide-bandgap perovskite solar cell according to claim 1, characterized in that, A transparent conductive electrode is disposed on the substrate, and the transparent conductive electrode is made of ITO.

4. The wide-bandgap perovskite solar cell according to claim 1, characterized in that, The hole transport layer is made of any one of 4PADCB, MeO-2PACz, or Me-4PACz.

5. The wide-bandgap perovskite solar cell according to claim 1, characterized in that, The electron transport layer is a composite structure of C60 / BCP / Ag.

6. The wide-bandgap perovskite solar cell according to claim 1, characterized in that, The metal electrode is made of silver, copper, or gold.

7. A method for preparing a wide-bandgap perovskite solar cell as described in any one of claims 1-6, characterized in that, Includes the following steps: (1) A transparent conductive electrode is fabricated on a substrate using radio frequency magnetron sputtering technology to obtain a transparent conductive substrate; (2) Prepare hole precursor solution. The hole precursor solution is spin-coated on a transparent conductive substrate using spin-coating technology and then annealed to prepare a hole transport layer. (3) A perovskite absorber layer is prepared by spin-coating a perovskite precursor solution onto the hole transport layer using spin-coating and vacuum flash evaporation techniques. The perovskite precursor solution contains a mixed chloride salt additive composed of MACl, PbCl2 and RbCl, wherein the amount of MACl added is 5 mol% of the total solute in the perovskite precursor, the amount of PbCl2 added is 2 mol% of the total solute in the perovskite precursor, and the amount of RbCl added is 2 mol% of the total solute in the perovskite precursor. (4) An electron transport layer is prepared on the perovskite absorber layer using thermal evaporation technology; (5) A metal electrode is prepared on the electron transport layer using thermal evaporation technology.

8. The preparation method according to claim 7, characterized in that, In step (3), the specific process for preparing the perovskite absorber layer is as follows: the perovskite precursor solution with mixed chloride salt additives is spin-coated onto the hole transport layer. The spin coating is carried out in two stages. The first stage has a rotation speed of 500 rpm and a duration of 5 to 10 s, and the second stage has a rotation speed of 4000 rpm and a duration of 15 to 25 s. After spin coating, vacuum flash evaporation is performed, the gas pressure is evacuated to 4 Pa ​​and maintained for 30 to 120 s, and then annealing is performed.

9. The preparation method according to claim 7, characterized in that, In step (1), the material of the transparent conductive electrode is ITO; in step (2), the material of the hole transport layer is one of 4PADCB, MeO-2PACz or Me-4PACz.

10. The preparation method according to claim 7, characterized in that, In step (4), the electron transport layer is a composite structure of C60 / BCP / Ag; in step (5), the material of the metal electrode is one of silver, copper or gold.